La narcoculture : vers un nouvel exotisme mexicain - Sébastien Rutés (Caravelle)
In the past, Latin-American intellectuals have complained about the representation of continental reality because it was reduced to stereotypes of magical realism. In Mexico, the same sort of criticism is now emerging denouncing the new reduction of national culture’s expression to drug-related cultural imagery. The study of North American mass cultural productions helps to understand the emergence of a new exoticism of violence based upon ancient representations of otherness, and contributes to create an alienating redefinition of the Mexican cultural identity from abroad.